The Development of Android-Based Mobile Learning for Indonesian History Course at Vocational High School - Heni Rita Susila; Yamanto Isa; Nina Ikhwati Wahidah (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2023)
This study aimed to develop android-based mobile learning for Indonesian History course at SMK YIS Martapura. This is a Research and Development (R&D) using the Alessi & Trollip model. Data collection techniques used questionnaire while research data were analyzed using the percentage formula. From the validation results, media experts scored got 88.69 percent belong to